Struktur Modal dan Nilai Perusahaan Manufaktur Di Indonesia - Teguh Erawati; Maria Kristianti Rika Nahak (Jurnal Simki Economic, 2023)
This study aims to examine whether there is an effect of manegerial ownership, profitability, capital structure on firm value. In food and beverage manufacturing companies listed on the Indonesia Stock Exachange for the 2015-2017 period. The determination of the sample was carried out using a purpose sampling technique and was obtained from 17 manufacturing companies with an observation period 3 years, namely from 2015-2017 so that the total sample obtained was 51 annual reports of food and beverage companies. From this study, different result were obtained between the three independent variables, where two variables did not have a significant effect and one variable had a significant effect. The manegerial ownership variable does not have a sicnificant effect on firm value. The profitability has a significant positive result on firm value and the capital structure variable does not have a significant effect on firm value.